Field study 4 : exploring the curriculum activity sheets - Reganit, Arnulfo Aaron R.; Gavino, Renato L. (Quezon City, Philippines : C&E Publishing, 2007)
Field study is intended to provide students with practical learning experiences through observation, verification, reflection on, and actual experiences of the different components of dynamic teaching- learning processes in the actual school settings.
Activity Sheet 1- The intention -- Activity sheet 2- The intention -- Activity sheet 3- The intention -- Activity sheet 3- The intention -- Activity sheet 4- The intention -- Activity sheet 5- The implementation -- Activity sheet 6- The implementation -- Activity sheet 6- the implementation -- Activity sheet 7- The implementation -- Activity sheet 8- The Implementation -- Activity sheet 9- The implementation -- Activity sheet 10- The implementation -- Activity sheet 11- The implementation -- Activity sheet 12- The implementation -- Activity sheet 13- The implementation
Keywords: EDUCATION -- PHILIPPINES